Determination of Internship Rules: Analysis Wages, Workload and Working Time - Setyo Widodo, Djoko (Dinasti Research, 2022)
Literature Review Article Determination of Internship Regulations: Analysis of Wages, Workload and Working Time is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Wages are related to Internship Rules; 2) Workload related to Internship Rules; and 3) Working Time related to Internship Rules. Apart from these 3 exogenous variables that affect the endogenous Internship Rules variables, there are still many other factors including Network, Experience and Training variables.